(untitled) (Journal of the College of Basic Education, 2026)
Klebsiella pneumoniae has emerged as a significant pathogen globally, particularly in clinical settings, resulting in severe infections, including UTI, respiratory tract infections, and bloodstream infections, and the high rates of resistance to the most common drugs make it very difficult to treat. Numerous characteristics that increase virulence are responsible for the observed pathogenesis of bacteria. This study aimed to investigate biofilm-forming ability among the collected isolates and the presence of the virulence gene (rmpA). And to determine gene association with increased biofilm formation. Methods: seventy-five clinical isolates were gathered from different clinical samples (urine, blood, sputum, and stool). Antibiotic susceptibility was tested against a number of commonly used medications, including beta-lactam antibiotics. Biofilm formation was evaluated using the plate assay method, and the presence of the targeted gene was determined by molecular analysis. Result: Most isolates showed high resistance to beta-lactams, with nearly eighty percent of them being resistant. Among the highly effective drugs were carbapenems (DOREBENEM)with (82.7%). And for the biofilm development test, it was shown that a total of 86.6% of the Klebsiella pneumoniae isolates were biofilm producers, ranging from weak to strong, while 13.4% did not produce biofilm. Additionally, the molecular level revealed a variable distribution of the targeted gene in the study, which indicates the presence of a virulent gene (rmpA) (58.6%). In conclusion, it has been demonstrated that Klebsiella pneumonia isolates exhibit a strong biofilm-forming capacity increased the rates of resistance to antibiotics. And concerning the relation with the rmpA gene, a positive association was detected between biofilm formation and rmpA-carrying isolates, although it was strain dependent. This indicates that multiple factors (genetic, environmental), rather than a single gene, can control the intricate processes of biofilm development.